2022
DOI: 10.1108/hff-01-2022-0034
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of forced convective nanofluid flow through a wavy channel with linearly varying amplitude at the entrance

Abstract: Purpose The purpose of this paper is to analyze the heat and momentum transfer for steady two-dimensional incompressible nanofluid flow through a wavy channel with linearly varying amplitude in the entrance region. Design/methodology/approach The mass, momentum and energy conservation equations for laminar flow of Cu-water nanofluids are computationally solved using the finite element method. A parametric study is carried out by varying the dimensionless length of the channel section with varying amplitude (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In addition, the performance factor for the present WCPB design is higher than that of the recent wavy channel with partially field porous media design (Kumar et al, 2022a(Kumar et al, , 2022bKumar and Pandey, 2022). As a result, the findings of the current work are recommended over the available design of wavy channel with partially filled porous media for suiatle HFF 33,6 design of effcient heat exchanging devices used for process plants, solar collectors and aerospace applications.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…In addition, the performance factor for the present WCPB design is higher than that of the recent wavy channel with partially field porous media design (Kumar et al, 2022a(Kumar et al, , 2022bKumar and Pandey, 2022). As a result, the findings of the current work are recommended over the available design of wavy channel with partially filled porous media for suiatle HFF 33,6 design of effcient heat exchanging devices used for process plants, solar collectors and aerospace applications.…”
Section: Discussionmentioning
confidence: 71%
“…Now, an effort has been made to compare the performance factor of WCPB with the existing recent designs of wavy channels with partially filled porous media. The comparison of performance factor of presented WCPB with the works of Kumar et al (2022aKumar et al ( , 2022b and Kumar and Pandey (2022) at different Darcy number is depicted in Figure 12. Kumar et al (2022aKumar et al ( , 2022b It is found that the performance factor of presented WCPB is higher by 24.44%, 12.02% and 40.83% for Da = 10 À4 , 10 À3 and 10 À2 , respectively, compared to results of Kumar et al (2022aKumar et al ( , 2022b.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations